A Case Report on Cervical Canal Stenosis Secondary to Ossification of Posterior Longitudinal Ligament - Lavanya, Korikani; Kavya, Galanki Arundathi; Muskan, Shaik; Chettri, Kriti Suberi; Rao, Chinta Nageswara (Journal of Pharmacy Practice and Community Medicine, 2026)
Cervical canal stenosis secondary to Ossification of the Posterior Longitudinal Ligament (OPLL) is a progressive condition that can lead to significant spinal-cord compression and neurological deficits. This case report describes a 57-year-old female who presented with back pain radiating to both lower limbs, associated with limb weakness, numbness, and difficulty in walking. The patient had a medical history of diabetes mellitus and hypertension. Clinical examination revealed reduced muscle power in both upper and lower limbs. Magnetic Resonance Imaging (MRI) of the cervical spine demonstrated multilevel (C3-C7) disc bulges with spinal-cord compression and features suggestive of OPLL, along with additional findings in the dorsal and lumbar spine. Based on clinical and radiological findings, a diagnosis of cervical canal stenosis secondary to OPLL was established. The patient underwent posterior cervical decompression with C3 to C7 laminectomy and lateral mass fusion. Postoperative management included antibiotics, analgesics, proton pump inhibitors, and supportive therapy. The patient showed gradual clinical improvement following surgical intervention. This case highlights the importance of early diagnosis, timely surgical management, and multidisciplinary care in improving outcomes in patients with OPLL-associated cervical canal stenosis.
Keywords: Cervical canal stenosis; Ossification of the posterior longitudinal ligament; Laminectomy